Analysis of MARIA Reactor Safety Based on Efficiency Measurement of Shim Rod Using Method of Fixed Period - Rachmatulloh, Hafizh Fatah; Siti Aisjah, Aulia; Pytel, Krzysztof (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2017)
An experiment was conducted in MARIA reactor as the part of reactivity measurement inside the reactor using method of fixed period while MARIA reactor was being started up. It was important as performance indicator that shim rod worked well and able to maintain reactivity on the level not exceeding the value of 1 by compensating the excess reactivity to provide reactor safety. The measurement was done directly at MARIA reactor control room on April 28th, 2015 using digital reactimeter, therefore, it allowed performing continuous measurement of reactor reactivity. Data at shim rod – 5 (PK-5) was collected, with time interval 0.49 S. Preliminary calculations were done by neglecting the presence of photoneutrons. For the result, at full shim rod insertion (1067 mm) absorbed reactivity with value 0,92 was obtained. The result showed that the shim rod worked well because the reactivity never exceeding 1. The result as an early parameter that guarantees MARIA reactor safety from burning out the claddings of fuel elements and radiological accident.